A study of incidence and outcome of acute kidney injury in common undifferentiated febrile illnesses - Cherian, Jacob; Deodhar, Divya (International Journal of Research in Medical Sciences, 2020)
Background: Patients presenting with acute undifferentiated febrile illness may have delay in diagnosis due to nonspecific symptoms and signs. Kidney injury in these patients can cause detrimental effect on their prognosis and hence early diagnosis is warranted. Methods: This is an observational prospective study conducted in the Department of Medicine at Christian Medical College and Hospital, Ludhiana for a period of one year from 1st November 2014 till 31st October 2015. Results: Among the 532 patients acute febrile illness included in the study, 437(82.1%) were diagnosed with dengue fever. A total of 190(35.7%) patients were diagnosed to have AKI. The incidence of AKI in specific diseases was found to be the highest in Malaria 8(61.5%) out of 13 patients). In AKI, majority of them were in the risk category with 97(51.0%). A total of 26(13.6%) patients with AKI required Hemodialysis. Among the 190 patients who had AKI 43(22.6%) died. Conclusions: Dengue was the most common acute febrile illness. Among the patients with acute kidney injury majority were in the risk category with 97(18.2%). 326(61.2%) patients were males with a male to female ratio was found to be 1.5: 1. Dengue with acute kidney injury had the most proportion of patients in the risk and injury category and malaria with acute kidney injury having the highest proportion in failure category. The highest incidence of patients with AKI requiring hemodialysis was seen in scrub typhus. Leptospirosis with AKI had the highest proportion of mortality. The failure category had the highest proportion of mortality.